(untitled) (Scientia Agropecuaria, 2025)
The presence of foliar phytopathogenic fungi causes severe damage to leave and fruits of peach (Prunus persica L.), in producing areas of southern Chihuahua, Mexico, which has caused a decrease in production by 30%. The objective of this work was to identify morphologically and molecularly the foliar phytopathogenic fungi associated with the peach tree crop, evaluating the pathogenicity in one-year-old plants against Trichoderma asperelloides. Leaves with brown and brown lesions were collected from mummified fruits on the plant from 19 commercial peach orchards distributed in three municipalities of regional and national production in the State of Chihuahua, Mexico. Fungal identification of four representative isolates was performed using morphological methods. characterization and phylogenetic analysis based on the internal transcribed spacer region (ITS1 and ITS4) of ribosomal DNA, part of the translation elongation factor 1-alpha (TEF) a second secondary primer for each of the genera for, Collectotrichum ACT-512F and ACT-583R, Fusarium with EF1. For plant confrontations, a concentration of 1x106 conidia was inoculated. mL-1 of pathogens such as T. asperelloides, evaluating leaf diameter and length, height, severity and incidence. It was possible to identify the presence of Fusarium sambucinum, Collectotrichum gleosporoides and Monilinia frutícola, in addition the B-F-M1-A2-ACCH-3 strain of F. Sambucinum obtained the highest values ​​in the inhibition of the response variables and in severity Monilinia frutícola presented 61.23% as the highest value. It is recommended to use strain 3 as a biological control of foliar phytopathogens.